Assessment on lead and cadmium pollution in tilapia and water spinach cultivated in Nhue River related to human health risk in Hanam - Luu Quoc Toan; Dang Xuan Sinh; Hung Nguyen-Viet; Nguyen Hung Long; Phuc Pham Duc (2014)
We used the Environment Health Risk Assessment framework to assess the health risks due to Pb and Cd in tilapia and water spinach caught/harvested along the Nhue River, in Kim Bang, Ha Nam in 2013. In total, 81 samples of water, tilapia and water spinach (27 of each) were taken from Nhue River and analysed for lead (Pb) and cadmium (Cd) pollution. 142 consumers were interviewed regarding the consumption levels of tilapia and water spinach. The analysis found that 100% samples of water spinach were contaminated with Pb and Cd; 100% and 96.3% of the tilapia samples were contaminated with Pb and Cd. The concentrations of Pb and Cd in water spinach were in the ranges of 29 – 385 µg/kg and 0.79 – 27 µg/kg. Their ranges in tilapia samples were 15 – 389 µg/kg and 0.12 – 8.8 µg/kg. The average consumptions of water spinach and tilapia were estimated at 108.9 g per meal and 132 g per meal, respectively. Local residents consumed 75 water spinach meals per year, therefore Pb and Cd intakes were 13.6 µg per week and 1.95 µg per month, respectively. For tilapia, the consumption frequency was 65 meals per year, Pb and Cd intakes were 9.7 µg per week and 1.88 µg per month, respectively. Most of the intake levels were lower than the recommended levels set by WHO. However, 14.08% of the surveyed residents had elevated Pb intakes from contaminated water spinach.